Transcranial Direct Current Stimulation Enhances Episodic Memory in Healthy Older Adults by Modulating Retrieval-Specific Activation - Lijuan Huo; Zhiwei Zheng; Jia Huang; Rui Li; Jin Li; Juan Li (Neural Plasticity)
Memory decline has become an issue of major importance in the aging society. Anodal transcranial direct current stimulation (atDCS) is a viable tool to counteract age-associated episodic memory deterioration. However, the underlying neural mechanisms are unclear. In this single-blind, sham-controlled study, we combined atDCS and functional magnetic resonance imaging to assess the behavioral and neural consequences of multiple-session atDCS in older adults. Forty-nine healthy older adults received either 10 sessions of anodal or sham stimulation over the left dorsolateral prefrontal cortex. Before and after stimulation, participants performed a source memory task in the MRI scanner. Compared to sham stimulation, atDCS significantly improved item memory performance. Additionally, atDCS significantly increased regional brain activity around the stimulation area in the prefrontal cortex and extended to the bilateral anterior cingulate cortex. Neural changes in the prefrontal cortex correlated with memory gains. Our findings therefore indicate that multiple-session offline atDCS may improve memory in older adults by inducing neural alterations.